2014
DOI: 10.1111/eea.12247
|View full text |Cite
|
Sign up to set email alerts
|

Areas of China predicted to have a suitable climate for Anoplophora chinensis under a climate‐warming scenario

Abstract: Anoplophora chinensis (Forster) (Coleoptera: Cerambycidae) is an A1 class quarantine pest, native to China, Japan, and North Korea. The A. chinensis outbreak in China has severely affected the local environment and economic development. This study investigates potential areas in China with suitable climate for A. chinensis using historical climate data and future climate-warming estimates generated by CLIMEX1.1. These future estimates are based on simulated climate data (2010-2039) provided by the Tyndall Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…The simulated climate data were generated by five climate-coupling models [HadCM3 (UK), PCM (USA), CGCM2 (Canada), CSIRO2 (Australia), and ECHAM4 (Germany)] using four greenhouse gas emission scenarios (A1FI, A2, B1, and B2). The TYN SC2.0 data set simulated five climate data sets for 2001–2100, which included the average daily temperature, diurnal temperature range, precipitation, vapor pressure, and cloudiness [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The simulated climate data were generated by five climate-coupling models [HadCM3 (UK), PCM (USA), CGCM2 (Canada), CSIRO2 (Australia), and ECHAM4 (Germany)] using four greenhouse gas emission scenarios (A1FI, A2, B1, and B2). The TYN SC2.0 data set simulated five climate data sets for 2001–2100, which included the average daily temperature, diurnal temperature range, precipitation, vapor pressure, and cloudiness [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The citrus long-horned beetle (CLB), Anoplophora chinensis (Forster) (Coleoptera: Cerambycidae) is a polyphagous wood-boring beetle native to China, Japan, and the Korean peninsula (Haack et al, 2010 ). This beetle has spread to Europe through international shipments of wood-packing materials and live plants from Asia and is a quarantine pest species on the European Union (EU) and European and Mediterranean Plant Protection Organization (EPPO) A1 list (Rizzi et al, 2013 ; Ge et al, 2014 ). It has a very broad range of host plants (>100 species from 19 families), of which 48 species are distributed in China (Ge et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This beetle has spread to Europe through international shipments of wood-packing materials and live plants from Asia and is a quarantine pest species on the European Union (EU) and European and Mediterranean Plant Protection Organization (EPPO) A1 list (Rizzi et al, 2013 ; Ge et al, 2014 ). It has a very broad range of host plants (>100 species from 19 families), of which 48 species are distributed in China (Ge et al, 2014 ). Larval infestation damages the vascular system and woody tissues of host plants, ultimately causing severe damage to ornamental and forest trees that may lead to mortality (Haack et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…During sampling of damaged trees, both females and males were detected, however, no eggs or larvae were found. Anoplophora chinensis, native to China, Japan, and North Korea (Ge et al, 2014), was first recording in Antalya in this study. While adults and evidence of their feeding were rarely observed on the upper parts of trees, both females and males were mostly detected around the exit holes (6-10 mm diameter) near the base of the trunk ( Figure 3); and it was observed that these adults could fly short distances when disturbed.…”
Section: Resultsmentioning
confidence: 78%